Health Educational Protocol for Calming Menopausal Stage Transition Among Premenopausal Women - Hefnawy, Gehan Refat; AL-Olimat, Kamlah Ahmed; Omara, Amany Lotfy; Mahfouz, Asmaa. K.; Mohamed, Hanaa Hamad (Journal of Ecohumanism, 2024)
Evaluate effect of Health educational protocol for Calming Menopausal stage Transition among premenopausal women. Quasi experimental study design, subject sixty-two women from obstetrics and gynecology out patients' clinics in in General Hospital of Kafre El-Sheikh city, 40 years old that categorized according to menopausal stages. Data was gathered at baseline and posttest done immediately after termination of the intervention while follow-up test done after a period of three months. Mean age of the participants was 51± 8.7, it was found that 93.5%, 77.4%, 74.2%, 71.0%, 67.7% and 22.6% were complaining of hot flushing, vaginal dryness, headache & constipation, urinary incontinence, nervousness & irritability, and vaginal bleeding respectively. A significant improvement was detected regarding the hot flushing, vaginal dryness, headache, constipation, nervousness, irritability and urinary incontinence. Also, knowledge, application of the Kegel exercise, the mind/body relaxation technique, and deep breathing exercises had highly significant between pre-test and follow-up test. In Conclusion, improvement was noted in women knowledge, skills, and menopausal problems after the implementation of the educational intervention. Recommendation: Health education programs should be carried out to improve knowledge and actions about menopausal health for safe and comfortable transition stage among Egyptian women.